1974
DOI: 10.1104/pp.53.4.653
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Respiratory Properties of Mitochondria Isolated from Developing Winter Wheat Seedlings

Abstract: The studies of Sarkissian and Srivastava (20,22) have demonstrated that excellent respiratory control indices and ADP:O ratios greater than the "theoretical" discussed by Lehninger (13) can be obtained from mitochondria of wheat seedlings. They have reported further (25) that respiratory control and ADP:O ratios decline with decreasing age of seedlings, and that these parameters are significantly greater in mitochondria from shoots than from roots or leaves. These investigations have demonstrated that the sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The observation that ca-ketoglutarate in the presence of ADP is oxidized rapidly with good respiratory control and close to theoretical ADP/O ratios (14) suggests that processes other than those normally associated with respiration are involved in mitochondrial contraction. This is supported further by the rapid decline observed in the contraction response when seedlings are grown at 2 C or transferred from 24 to 2 C, although previous studies (11) have demonstrated good respiratory properties of mitochondria isolated from 2 C grown seedlings.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The observation that ca-ketoglutarate in the presence of ADP is oxidized rapidly with good respiratory control and close to theoretical ADP/O ratios (14) suggests that processes other than those normally associated with respiration are involved in mitochondrial contraction. This is supported further by the rapid decline observed in the contraction response when seedlings are grown at 2 C or transferred from 24 to 2 C, although previous studies (11) have demonstrated good respiratory properties of mitochondria isolated from 2 C grown seedlings.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondria were isolated by the procedure of Miller et al (12) using media previously described (14). Swelling and contraction of mitochondria, as indicated by light scattering (18), were followed at 24 C by measuring changes in absorbance at 520 nm on either a Beckman DK or a Gilford 2000 spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen uptake was measured polarographically at 24 C with a conventional Clark electrode using media and methods previously described (22 Figure 1A and The addition of dinucleotides, in the absence of exogenous ADP did not stimulate 02 consumption (Fig. 1, B, C, and D).…”
Section: Methodsmentioning
confidence: 99%
“…Rideau) were germinated and grown in the dark at 24 C on moist filter paper for 2 days. Mitochondria were isolated from the shoots by differential centrifugation (22) and where indicated, further purified by sucrose density gradient centrifugation. Sucrose gradients were prepared by layering 3.7 ml each of 0.8, 1.0, 1.2, 1.4, 1.6, 1.8, and 2 M sucrose solutions containing 10 mm KCl, 10 mm tris-HCl 10 mM KH2PO4, and 0.75% (w/v) BSA at pH 7.2 in 30-ml centrifuge tubes and stored 24 hr at 2 C to produce a linear gradient.…”
Section: Methodsmentioning
confidence: 99%